T cells that are naturally tolerant to cartilage-derived type II collagen are involved in the development of collagen-induced arthritis - Malmström, Vivianne (BioMed Central, 2000)
INTRODUCTION: A discussion is ongoing regarding the possible role of cartilage-directed autoimmunity as a part of the pathogenesis of rheumatoid arthritis (RA). One possibility is that the association of RA with shared epitope-expressing DR molecules reflects a role for major histocompatibility complex (MHC) class II molecules as peptide receptors, and that the predilection of the inflammatory attack for the joint indicates a role for cartilage as a source of the antigenic peptides. A direct role for CII in the development of arthritis is apparent in the CIA model, in which a definite role for MHC class II molecules and a role for CII-derived peptides have been demonstrated [1,2,3]. Remarkably, it was found that the identified MHC class II molecule in the CIA model A(q) has a structurally similar peptide binding pocket to that of the shared epitope, expressing DR4 molecules [4]. In fact, DR4 (DRB1(*)0401) and DR1 (DRB1(*)0101) transgenic mice are susceptible to CIA because of an immune response to a peptide that is almost identical to that which is involved in A(q)-expressing mice [5,6]. They are both derived from position 260-273 of the CII molecule; the peptide binds to the A(q)molecule with isoleucine 260 in the P1 pocket, but with phenylalanine 263 in the P1 pocket of the DR4 and DR1 molecules. Although these findings do not prove a role for CII in RA, they show that such recognition is possible and that there are structural similarities when comparing mouse with human. However, there are also strong arguments against such a possibility. First, arthritis can evolve without evidence for a cartilage-specific autoimmunity, as seen with various adjuvant-induced arthritis models [7,8] and in several observations using transgenic animals with aberrant immunity to ubiquitously expressed proteins [9,10,11]. Moreover, the MHC association in the adjuvant arthritis models correlates with severity of the disease rather than susceptibility [7,8], as has also been observed in RA [12]. Second, it has not been possible to identify the CII-reactive T cells from RA joints, or to achieve a strong and significant CII proliferative response from T cells derived from RA joints. Most recently these negative observations were corroborated using DR4+CII peptide tetramer reagents [13]. On the other hand, it has also been difficult to isolate autoreactive CII-specific T cells from CIA, and it can be anticipated that, even in the CIA model, T cells that are specific for CII will be hard to find in the joints [4]. We believe that the explanations for these observations in both experimental animals and humans are related to tolerance. The CIA model in the mouse is usually induced with heterologous CII, and is critically dependent on an immune response to the glycosylated CII peptide 256-270, which is bound to the MHC class II A(q) molecule. In CII transgenic mice, expressing the heterologous (rat) form of the immunodominant CII 256-270 epitope in cartilage, we observed partial T-cell tolerance. This tolerance is characterized by a low proliferative activity, but with maintained effector functions such as production of IFN-γ and the ability to give help to B cells to produce anti-CII IgG antibodies [14]. Interestingly, these mice were susceptible to arthritis. However, a possibility was that T cells that had newly emerged from the thymus and that were not yet tolerized when the mice were immunized with CII led to the induction of arthritis. We have now addressed this possibility and found that induction of tolerance occurs within a few days, and that mice lacking recent thymic emigrants (ie thymectomized mice) display partially tolerant T cells and susceptibility to arthritis to the same extent as nonthymectomized mice. In addition we found that T cells that are reactive with the nonmodified peptides are relatively more affected by tolerance than T cells that are reactive with the more immunodominant glycosylated variants. OBJECTIVES: To investigate the possibility that T cells that are naturally tolerant to the cartilage protein CII are involved in the development of arthritis, and to exclude a role for nontolerized recent thymic T-cell emigrants in the development of arthritis. MATERIALS AND METHODS: A mutated mouse CII, expressing glutamic acid instead of aspartic acid at position 266, was expressed in a transgenic mouse called MMC (mutated mouse collagen) that has been described earlier [14]. The mice were thymectomized, or sham-operated, at 7 weeks of age and allowed to recover for 4 weeks before being immunized with rat CII in complete Freund's adjuvant. Arthritis development was recorded and sera analyzed for anti-CII IgG, IgG(1) and IgG(2a) levels. To assay T-cell effector functions, other MMC and control mice were immunized in the hind footpads with rat CII in complete Freund's adjuvant, and the draining popliteal lymph nodes were taken 10 days later. The lymph node cells (LNCs) were used for proliferation assay, IFN-γ enzyme-linked immunosorbent assay (ELISA) and B-cell enzyme-linked immunospot (ELISPOT). For the proliferation assay, 10(6) cells were put in triplicate cultures in microtitre wells together with antigen and incubated for 72h before thymidine-labelling and harvesting 15-18h later. For IFN-γ ELISA analysis, supernatant from the proliferation plates was removed before harvesting and used in an ELISA to quantify the amount of IFN-γ produced [15]. B-cell ELISPOT was performed to enumerate the number of cells producing anti-CII IgG [16]. T-cell lines that were reactive towards rat CII were established by immunization with rat CII. An established T-cell line that was reactive with CII and specific for the CII 256-270 peptide was restimulated with freshly collected, irradiated, syngenic spleen cells and rat CII for 3 days followed by 2 weeks of IL-2 containing medium. Immediately before transfer, the cells were labelled with the cytoplasmic dye 5 (and 6)-carboxyfluorescein diacetate succinimidyl ester (CFSE) [17]. Labelled cells (10(7)) were injected intravenously into transgenic MMC mice and nontransgenic littermates. The mice were killed 4 days after cell transfer, and the concentration of CFSE-labelled cells was determined by flow cytometry. RESULTS AND DISCUSSION: To investigate whether and how quickly CII-reactive T cells will encounter CII in vivo, an established T-cell line that is reactive towards rat CII was labelled with the cytoplasmic dye CFSE and transferred into MMC-QD and control mice. Four days later the mice were killed, and it was found that MMC-transgenic mice had dramatically fewer CFSE-labelled cells in the spleen than did nontransgenic littermates (0.11% compared with 0.57%). Similarly, reduced numbers of CFSE-positive cells were observed in blood. This indicates that the T cells encountered the mutated CII that was present in the cartilage of MMC mice, but not in the nontransgenic littermates. Presumably, CII from cartilage is spread by antigen-presenting cells (APCs) to peripheral lymphoid organs. This observation also suggests that newly exported T cells from the thymus will be tolerized to CII in the periphery within less than 4 days. To further investigate whether the MMC mice harbours naïve or tolerized T cells, the mice were immunized with CII at different time points after thymectomy that were well in excess of the times required for their encounter with CII. After 10 days, the response was analyzed in vitro towards both the nonglycosylated and the glycosylated CII 256-270 peptides as well as towards purified protein derivative. The galactosylated form of the peptide (Fig. 1) was used because this is the most immunodominant modification [18]. In contrast to control mice, LNCs from transgenic mice did not proliferate significantly towards the nonglycosylated peptide, indicating that these cells have been specifically tolerized, which is in accordance with earlier observations [14]. A reduced, but still significant proliferation was also observed toward the immunodominant glycosylated CII peptide. Most important, however, was that the proliferative response in the MMC mice did not decrease after thymectomy. Similarly, a significant IFN-γ production towards the glycosylated CII peptide was observed in the MMC mice. The response was somewhat reduced compared with that observed in nontransgenic littermates, and this was especially true for the response toward the nonglycosylated peptide. Again, no decrease in the MMC response by thymectomy was observed. Taken together, the T-cell response in transgenic mice was reduced in comparison with that in the nontransgenic littermates. Furthermore, the response in transgenic animals did not decrease by thymectomy (4 or 8 weeks before immunization), showing that autoreactive T cells are still maintained (and partially tolerized) with significant effector functions at least up to 8 weeks after thymectomy, excluding a exclusive role for recent thymic emigrants in the autoimmune response towards CII. To investigate whether thymectomized mice, lacking recent CII-specific thymic emigrants, were susceptible to CIA, mice were immunized with CII 4 weeks after thymectomy and were observed for arthritis development during the following 10 weeks. Clearly, the thymectomized MMC mice were susceptible to arthritis (five out of 18 developed arthritis; Fig. 2), and no significant differences in susceptibility between thymectomized and sham-operated mice, or between males and females, were seen. In accordance with earlier results [14], MMC transgenic mice had a significantly reduced susceptibility to arthritis as compared with the nontransgenic littermates (P < 0.0001 for arthritic scores, disease onset and incidence). All mice were bled at 35 days after immunization, and the total levels of anti-CII IgG were determined. Transgenic mice developed levels of anti-CII IgG significantly above background, but the antibody titres were lower than in nontransgenic littermates (P < 0.0001). No effect on the antibody levels by thymectomy was observed, nor did thethymectomy affect the distribution of IgG(1) versus IgG(2a) titres,indicating that the observed tolerance is not associated with a shift from a T-helper-1- to a T-helper-2-like immune response. These findings show that T cells that are specific for a tissue-specific matrix protein, CII, are partially tolerized within a few days after thymus export and that these tolerized cells are maintained after thymectomy. Most important, mice that lack newly exported CII reactive T cells are still susceptible to CIA, suggesting that the partially tolerant T cells are involved in development of arthritis. In the light of these data it is possible to explain some of the findings in RA. T-cell reactivity to CII has been shown in RA patients, but with a very weak proliferative activity [19,20]. This is fully compatible with observations in mouse and rat CIA when autologous CII, and not heterologous CII, are used for immunization. This is particularly true if the responses are recorded during the chronic phase of disease, in which the antigen-specific T-cell responses seem to be suppressed in both humans and experimental animals. These observations were confirmed in a recent report [21] in which it was shown that CII-reactive T-cell activity could be detected in RA patients if IFN-γ production but not proliferation was measured. In the present studies in mice the strongest response is seen towards post-translational modifications of the peptide. Because the T-cell contact points are the same whether the peptide is bound to DR4 or to A(q), it is fully possible that post-translational modifications of the peptide also plays a significant role in humans [22]. The fact that IgG antibodies specific for CII are found in many RA patients could be explained by maintained B-cell helper functions of CII-reactive T cells. In fact, it has been reported [23,24] that the occurrence of IgG antibodies to CII is associated with shared epitope DR4 molecules. These observations are thus compatible with a role for CII reactivity in RA. To avoid any confusion, it needs to be stressed that RA is a heterogeneous syndrome in which not only CII, but also other cartilage proteins and other mechanisms are of importance. Such a pathogenic heterogeneity is reflected by the multitude of experimental animal models that have demonstrated how many different pathways may lead to arthritis [25].